PENGARUH KINERJA BANK ATAS DANA PIHAK KETIGA - Rasyid, Rosmita (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2017)
Bank capital structure comes more from the third party fund than banking owner. Banking customers is almost impossible to control the actions of managers in the distributions of funds. Control of banking operations regulated by several provisions made by monetary authorities. Banking customers can monitor the progress by viewing the performance of the bank. The purpose of this study is to see how the performance of the bank influent the third party fund. Bank performance variables are NPL (Non Performing Loan), NIM (Net Interest Margin) dan LDR (Loan to Deposit Ratio) dan third party fund variables are Savings and Deposits. This study uses data that is state-owned bank in Indonesia in 2003-2012.The data were analyzed by EVIEWS program. The results showed that NPL does not significantly influence the placement of customers funds, but, NIM have positive affect and LDR have negative affect. The results of this study are expected to contribute for the customers in deciding the placement of funds in the bank and for the IAI compartments and OJK to set accounting standards to improve the quality of reporting banksKeywords: Bank Performance, LDR, NIM, NPL, Third Party Fund